The night of the San Vito flowers. When Lombardy discovered the Mazzaferro clan (Rivista di Studi e Ricerche sulla criminalità organizzata, 2019)
This arrest warrant brings to light the presence of the Mazzaferro’s clan in Lombardy. This clan has gradually become autonomous from the ‘ndrangheta and nevertheless it can be considered a direct emanation of the Calabrian mafia organization. The investigation sees the members of the clan condemned for the crime of mafia-type association and also has the merit of denying the thesis of the absence of collaborators of justice within the ‘ndrangheta.
Keywords: mafia-type organization; ‘ndrangheta; Mazzaferro; Lombardy; collaborators of justice